Porphyromonas gingivalis-Induced Cognitive Impairment Is Associated With Gut Dysbiosis, Neuroinflammation, and Glymphatic Dysfunction - Chi, Li; Cheng, Xiao; Lin, Lishan; Yang, Tao; Sun, Jianbo; Feng, Yiwei; Liang, Fengyin; Pei, Zhong; Teng, Wei (Frontiers in Cellular and Infection Microbiology, 2021)
Background Periodontal pathogen and gut microbiota are closely associated with the pathogenesis of Alzheimer’s disease (AD). Porphyromonas gingivalis (Pg), the keystone periodontal pathogen, can induce cognitive impairment. The gut has a connection and communication with the brain, which is an important aspect of the gut–brain axis (GBA). In the present study, we investigate whether Pg induces cognitive impairment through disturbing the GBA. Methods In this study, Pg was orally administered to mice, three times a week for 1 month. The effects of Pg administration on the gut and brain were evaluated through behaviors, gut microbiota, immune cells, glymphatic pathway clearance, and neuroinflammation. Results Pg induced cognitive impairment and dysbiosis of gut microbiota. The α-diversity parameters did not show significant change after Pg administration. The β-diversity demonstrated that the gut microbiota compositions were different between the Pg-administered and control groups. At the species level, the Pg group displayed a lower abundance of Parabacteroides gordonii and Ruminococcus callidus than the control group, but a higher abundance of Mucispirillum schaedleri. The proportions of lymphocytes in the periphery and myeloid cells infiltrating the brain were increased in Pg-treated animals. In addition, the solute clearance efficiency of the glymphatic system decreased. Neurons in the hippocampus and cortex regions were reduced in mice treated with Pg. Microglia, astrocytes, and apoptotic cells were increased. Furthermore, amyloid plaque appeared in the hippocampus and cortex regions in Pg-treated mice. Conclusions These findings indicate that Pg may play an important role in gut dysbiosis, neuroinflammation, and glymphatic system impairment, which may in turn lead to cognitive impairment.